Innovations in Computer Science and Engineering Proceedings of the Sixth ICICSE 2018 - Saini, H. S.; Sayal, Rishi; Govardhan, Aliseri; Buyya, Rajkumar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book includes high-quality, peer-reviewed research papers from the 6th International Conference on Innovations in Computer Science & Engineering (ICICSE 2018), held at Guru Nanak Institutions, Hyderabad, India from August 17 to 18, 2018. The book discusses a wide variety of industrial, engineering and scientific applications of the emerging techniques and offers a platform for researchers from academia and industry to present their original work and exchange ideas, information, techniques and applications in the field of computer science.
Named Entity Recognition in Tamil Language Using Recurrent based Sequence Model -- Quantum Digital Signature based Group Key Management in E-Commerce -- Predicting the Risk of Readmission of Diabetic Patients Using Deep Neural Networks -- Reliable Healthcare Monitoring System Using SPOC Framework -- Computer Aided Lung Parenchyma Segmentation Using Supervised Learning -- Gender Identification of Code Mixed Malayalam-English Data from WhatsApp -- Comparative Study of Machine Learning Approaches for Heart Transplantation -- Enhanced Trust based Cluster Head Selection in Wireless Sensor Networks -- Homomorphic Encryption Scheme to Enhance the Security of Data -- An Effective Data Transmission Approach through Cascading of Clusters in Path Identification for WSN Routing -- An Inception towards better Classification Technique for Big Data -- A Hybrid Feature Selection Approach for Handling a High Dimensional Data -- Improved Clustering Technique Using Meta Data for Text Mining -- Privacy Preservationin Healthcare by Process Mining.
Keywords: Telecommunication; Data protection; Computational intelligence; Communications Engineering, Networks; Data and Information Security; Computational Intelligence